The Effect of Niobium and Rubidium Doping on the Energy Band Gap of a Lithium Tantalate (LiTaO3) Thin Film - Agus Ismangil; Fatimah Arofiati Noor; Toto Winata (Institut Teknologi Bandung, 2021)
Chemical solution deposition (CSD) is a technique for making a film by keeping synthetic arrangements on the outer layer of the substrate. The outcomes show that the band gap energy of the LiTaO3 film is 1 eV. Electrons are more effectively invigorated to the valence band than to the conduction band on the grounds that the energy required is not excessively huge. Niobium-doped LiTaO3 film has a band gap energy of 1.15 eV. A large amount of energy is needed for electrons to be energized from the valence band to the conduction band. The rubidium-doped LiTaO3 film has a band gap energy of 1.30 eV.